Pengembangan Media Pembelajaran Matematika Berbasis Permainan Kartu 24 Game Uno untuk Meningkatkan Kemampuan Operasi Hitung Bilangan Bulat Siswa (Lembag, 2026)
This research was motivated by students' low interest in mathematics, particularly in integer arithmetic operations. The objective of this study was to develop a valid, practical, and effective instructional media based on the 24-game UNO card game for use in learning activities. This research was conducted through research and development (R&D) using the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects were seventh-grade students at SMPN 9 Pasuruan. Data collection techniques used validation sheets, practicality questionnaires, and learning outcome tests. Data analysis was conducted using descriptive, quantitative, and qualitative methods. The results showed that validation from material experts and media experts achieved an average score of 91.88%, categorized as very valid. Practicality based on teacher and student responses achieved an average score of 91.42%, categorized as very practical. The results of the learning outcome test (posttest) showed an average score of 85, categorized as effective. Thus, the mathematics learning media based on the 24 Game UNO card game is declared valid, practical, and effective for use in the learning process.